Effect of Early Prosthetic Fitting in patients with Below-Knee Amputation - Pervaiz, Tayyeba; Saleem, Saad; Tahir, Muhammad; Ahsan, Zarafshan; Kamran, Muhammad; Ahmed Khan, Aqeel; Rasool, Arsalan (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To evaluate the effect of early prosthetic fitting on patients with below-knee amputation. Methods: A cross-sectional research design was applied in this study. A total of 50 questionnaires were filled out by participants who met the inclusion criteria. Results: Slightly over 42% of the sample fell within the 30–40 age bracket and 32% fell within the 40–50 age bracket. The sample consisted of 42% females and 58% males, which is standard for amputation research. Regarding participants' levels of education, 68% had completed high school, 20% had completed primary school, and 12% had completed college or graduate level. Sixty-eight percent of the respondents reported for being unwell at the moment, with diabetes affecting 38% and hypertension 40%. The marital status breakdown was as follows: divorced 8%, separated 38%, married 48% and single 6%.Correlation analysis revealed a moderate positive connection (r = 0.400, p < 0.01) between Quality of Life (FQL) and Experience with Patients (EX). There was a significant positive correlation (r = 0.590, p < 0.01) between FQL and SAT, the Satisfaction test. Additionally, the Satisfaction test and EX showed a moderately favorable connection (r = 0.363, p < 0.01). The regression analysis indicated that the quality of life for below-knee amputees is positively and significantly correlated with early prosthetic fitting. With an F-statistic of 25.58 and an R-squared value of 0.35, early prosthetic fitting explains 35% of the variation in quality of life. The beta coefficient was 0.59, with a T-statistic of 5.06, indicating statistical significance Conclusion: Patients who receive early prosthetic fittings report higher levels of satisfaction with their lives and their prosthetics compared to those whose fittings are delayed. This study highlights the importance of early prosthetic fitting for improving the quality of life in below-knee amputees.